2016
DOI: 10.1080/07481187.2016.1237591
|View full text |Cite
|
Sign up to set email alerts
|

A consensual qualitative research analysis of the experience of inmate hospice caregivers: Posttraumatic growth while incarcerated

Abstract: A growing number of correctional facilities train inmates to provide end-of-life care for dying inmates. This study explores the phenomenological perspective of inmate-caregivers participating in an inmate-facilitated hospice program (IFHP) with regard to meaning and purpose in life, attitudes on death and dying, and perceived personal impact of participation. Twenty-two inmate-caregivers were interviewed at a maximum-security state correctional facility in the United States. The interviews were transcribed ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 36 publications
0
26
0
Order By: Relevance
“…The review identified 23 articles, 16 reporting qualitative methods2 3 29–42(table 3), six reporting quantitative methods8 9 43–46(table 4) and one reporting mixed methods4(table 3). Methodological diversity was high across all groups.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The review identified 23 articles, 16 reporting qualitative methods2 3 29–42(table 3), six reporting quantitative methods8 9 43–46(table 4) and one reporting mixed methods4(table 3). Methodological diversity was high across all groups.…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen articles reported findings from six studies based in the USA,8 9 29–33 36 39–43 four articles reported findings from three studies based in the UK,4 35 38 45 three articles reported findings from two studies based in Switzerland,3 34 37 two articles reported findings from one study in France2 46 and one article reported findings from a study in India 44. The articles reported on a broad range of areas, including prison healthcare facilities,43 45 the health of dying prisoners and causes of death,8 9 44 46 elderly and dying prisoners views on issues related to palliative and end of life care in prisons3 4 34 36 40 and inmate volunteer caregivers 30–33 42. Of the 19 studies which sampled prisoners (or their case records),2–4 8 9 29–34 36–38 40–42 44 46 12 dealt exclusively with male prisoners,4 8 29 30 32 33 36–38 40–42 and seven with male and female prisoners 2 3 9 31 34 44 46…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The team coded transcripts using a deductive approach guided by the COM-B as a coding framework. The coding process was guided by consensual qualitative research (CQR) procedures [30]. First, each team member read three transcripts independently and identi ed preliminary codes.…”
Section: Qualitative Studymentioning
confidence: 99%